1992
DOI: 10.1093/rheumatology/31.8.555
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Myelitis in Systemic Lupus Erythematosus: Two Cases With Magnetic Resonance Imaging

Abstract: Transverse myelitis is one of the most serious neurological complications occurring in the course of systemic lupus erythematosus. We describe two lupus patients, with transverse myelitis, one of whom had associated optic neuritis. In both, magnetic resonance imaging of the spinal cord showed an abnormal signal. In one case a good response to steroid and immunosuppressive therapy was observed; the other case failed to improve despite the therapy applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…11,[20][21][22][23] Spinal cord abnormalities in patients with inflammatory disorders and cerebrovascular diseases have been reported to frequently differ from those seen in patients with MS. 22,[24][25][26][27][28][29][30][31][32][33] Although our cohort of patients with newly diagnosed MS showed many brain lesions, in a substantial number of patients, brain MRI alone was, according to published criteria, insufficient for radiologic documentation of MS. In this patient, brain examination showed multiple focal lesions on characteristic locations for MS, a combination not observed in those with Devic's neuromyelitis optica.…”
Section: Materials and Methods Study Groupmentioning
confidence: 99%
“…11,[20][21][22][23] Spinal cord abnormalities in patients with inflammatory disorders and cerebrovascular diseases have been reported to frequently differ from those seen in patients with MS. 22,[24][25][26][27][28][29][30][31][32][33] Although our cohort of patients with newly diagnosed MS showed many brain lesions, in a substantial number of patients, brain MRI alone was, according to published criteria, insufficient for radiologic documentation of MS. In this patient, brain examination showed multiple focal lesions on characteristic locations for MS, a combination not observed in those with Devic's neuromyelitis optica.…”
Section: Materials and Methods Study Groupmentioning
confidence: 99%
“…Spinal cord abnormalities have been reported in inflammatory disorders and cerebrovascular disease, though the appearance of such abnormalities may differ from those seen in MS (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Little is known about the frequency of spinal cord abnormalities in inflammatory disorders and cerebrovascular disease.…”
mentioning
confidence: 99%
“…The role of steroid treatment for ATM is controversial. Some studies and case reports have noted a beneficial effect after treatment with steroids, while others were inconclusive, and some found no effect at al [4,[12][13][14][15][16][17][18][19]. Recent studies have suggested that highdose m-PSL was effective in the treatment of ATM in children [20,21].…”
Section: Discussionmentioning
confidence: 99%